Use of peripherally inserted central venous catheters (PICCs) in children receiving autologous or allogeneic stem-cell transplantation. Issue 2 (March 2018) - Benvenuti, Stefano; Ceresoli, Rosanna; Boroni, Giovanni; Parolini, Filippo; Porta, Fulvio; Alberti, Daniele
Introduction: The aim of our study was to present our experience with the use of peripherally inserted central catheters (PICCs) in pediatric patients receiving autologous or allogenic blood stem-cell transplantation. The insertion of the device in older children does not require general anesthesia and does not require a surgical procedure. Methods: From January 2014 to January 2017, 13 PICCs were inserted as a central venous device in 11 pediatric patients submitted to 14 autologous or allogeneic stem-cell transplantation, at the Bone Marrow Transplant Unit of the Children's Hospital of Brescia. The mean age of patients at the time of the procedure was 11.3 years (range 3-18 years). PICCs remained in place for an overall period of 4104 days. All PICCs were positioned by the same specifically trained physician and utilized by nurses of our stem-cell transplant unit. Results: No insertion-related complications were observed. Late complications were catheter ruptures and line occlusions (1.2 per 1000 PICC days). No rupture or occlusion required removal of the device. No catheter-related venous thrombosis, catheter-related bloodstream infection (CRBSI), accidental removal or permanent lumen occlusion were observed. Indications for catheter removal were completion of therapy (8 patients) and death (2 patients). Three PICCs are currently being used for blood sampling in follow-up patients after transplantation. Conclusions: Our data suggest that PICCs are a safe and effective alternative to conventional central venous catheters even in pediatric patients with high risk of infectious and hemorrhagic complications such as patients receiving stem-cell transplantation.